Zen-Inspired Interior Design in Residence - Aalia Khan; Deepti Pande Rana; Prof Suparna Sircar (International Journal of Urban Design and Development, 2023)
‘Zen’, a word derived from Buddhist philosophy indicates meditation, peacefulness, and harmony with natural elements. Zen-Inspired-Interior-design has commonly been used in Chinese and Japanese homes for several years but is now growing in popularity across several countries. Japanese interiors have several characteristics, the most important of them being minimalism i.e., using simple, lowlying furniture and a neutral colour palette with less ornament or heavy patterns and emphasis on functionality. It encourages the use of natural materials like wood and stone which bring nature indoors along with greenery inside and around the home. It is all about promoting a healthy and efficient way of life through closeness to nature, open, functional, and flexible spaces, and creating a soothing environment with subtle details. This research work delves into the various characteristics and concepts associated with Zen and Japanese-Inspired-Interiors. It also involves a study of the spatial layout and features of a traditional Japanese home and also draws parallels with the design of traditional Indian homes. The study also explores several literature studies that show the implementation of Japanese design in traditional as well as modern homes. The research helped in understanding how to take inspiration from the traditional Japanese way of designing, to create a home that acts as a tranquil solace and is both calming and rejuvenating, away from the chaos in this fast-paced world.
Keywords: Japanes; Japanese design; Zen; interior design; residential design